Dari Transendensi ke Transformasi: Krisis Epistemologis dan Rekonstruksi Paradigma Humanistik–Spiritual dalam Membumikan Nilai Transendental - Nurul Himmatul Qomaria; Vidya Dzurotun Nafisa; Adinda Auliya Saskiya Citra; Siti Nurul Faricha; Ali Hasan Siswanto (Sociale : Journal of Social Science, 2026)
This study aims to reconstruct a new paradigm capable of bridging the existing gap. Theoretically, it integrates the concept of transcendental values in Sufism with the humanistic–existential psychology approach and social transformation theory. The method employed is qualitative research based on library studies with philosophical, theological, and interdisciplinary approaches, analyzed through hermeneutic-critical methods and conceptual synthesis. The main argument of this study is that authentic social transformation can only be realized through the integration of inner transformation and structural change, mediated by transcendental awareness and human self-actualization. Therefore, transcendental values must be reconstructed not merely as norms, but as epistemic and practical energy. The scientific contribution of this research lies in the formulation of a humanistic–spiritual–transformative paradigm, the strengthening of the concept of spiritual agency, and the development of methodologies for applying transcendental values based on existential experience. This paradigm is expected to enrich the field of Islamic Studies while providing an alternative response to contemporary humanitarian crises.